A math student has a plan to solve the following system by the elimination method. to eliminate the x-term , he wants to multiply the top equation by 7. what should he multiply the second equation by so that when he adds the equation, the x-term are eliminated ? -3x-7y=-56-7x+10y=-1

Answers

Answer 1
Answer:

9514 1404 393

Answer:

  -3

Step-by-step explanation:

The coefficients of the x-terms are (-3, -7). If you swap them, you have (-7, -3). Negating one of them will give you (7, -3) or (-7, 3). Either of these pairs of multipliers will work to eliminate the x-terms.

The problem statement tells us the multiplier of the first equation is 7, so the multiplier of the second equation needs to be -3.


Related Questions

Solve for x: 3x − 24 = 81 57/3 105/3 57 105
A 30-ft. ladder makes an angle of 60 degrees with the horizontal when it reaches a given spot on a wall. What angle will a 35-ft. ladder make the horizontal if it reaches the sample spot?
Is 11.34 greater or less than 11.340
Brand X batteries have a mean life span of 102 hours, with a standard deviation of 6.8 hours. Brand Y batteries have a mean life span of 100 hours, with a standard deviation of 1.4 hours. Complete each of the sentences.
Need answer now in 10 min!!!

Use the data set to create a quadratic function if it applies. Use the model to predict the value of x when y = -4. (-3, 10), (0, 4), (3, -1), (6, -5), (9, -8)


Question 3 options:

A)

29.32 and 3.97


B)

32.27 and 4.57


C)

27.48 and 5.20


D)

No Solution

Answers

Answer:

The closest choice is ...

C)  27.48 and 5.20

Step-by-step explanation:

Using the equation ...

  y = ax² + bx + c

You can substitute the first three points to get linear equations in a, b, and c.

  10 = a(-3)² +b(-3) +c = 9a -3b +c

  4 = a(0)² + b(0) +c = c

  -1 = a(3)² + b(3) +c = 9a +3b +c

The second equation tells us c=4. Subtracting the first equation from the last, we get ...

  (9a +3b +c) -(9a -3b +c) = (-1) -(10)

  6b = -11

  b = -11/6

Then we can find "a" from the first equation:

  10 = 9a -3(-11/6) +4

  1/2 = 9a . . . . subtract 19/2

  1/18 = a . . . . . divide by 9

The model is ...

  y = (1/18)x² -(11/6)x +4 . . . . . . . . [call this "model A"]

  y = (x² -33x +72)/18

Solving this for y = -4, we have ...

  -4 = (x² -33x +72)/18

  x² -33x +144 = 0 . . . . . . multiply by 18, add 72

  (x -16.5)² -128.25 = 0 . . . . put in vertex form

  x = 16.5 ±√128.25 ≈ {5.17525, 27.8248}

___

The closest values to these among the choices offered are those of choice C. It appears that the coefficients of model A were rounded to 3 decimal places (or so) before the predicted x-values were computed.

Find the probability for choosing a letter at random from the word: Probability P(not P) A.) 1/11 B.) 2/11 C.) 5/11 D.) 10/11​

Answers

Answer:

D.) 10/11

Step-by-step explanation:

Here the given word Probability has 11 letters in it. And we have to calculate the Probability of not selecting a letter P from the above word.

So the formula for calculating any probability is Total Favorable outcomes / Total number of outcomes.

Here total number of outcomes are 11 as word Probability has 11 letters.

So the probability of selecting letter P from word Probability =  (1)/(11)

Now the P(not P) = 1 - P(selecting letter P)

                            = 1 - (1)/(11) = (10)/(11)

5. MAPPING Ben and Kate are making amap of their neighborhood on a piece of
graph paper. They decide to make one
unit on the graph paper correspond to
100 yards. First, they put their homes
on the map as shown below.

a. How many yards apart are Kate's and Ben's homes?

b. Their friend Jason lives exactly halfway between Ben and Kate. Mark the location of Jason's home on the
map. if my answers are wrong, correct me. i just used a pdf and idk if they’re right. ty ❤️

Answers

Answer:

a. 1,000 yards

b. (2, -1)

Step-by-step explanation:

Coordinates of Ben's House = (6, 2)

Coordinates of Kate's House = (-2, -4)

a. Number of yards between Kate and Ben's House using instance formula, d = √((x_2 - x_1)^2 + (y_2 - y_1)^2).

d = √((6 -(-2))^2 + (2 -(-4))^2)

d = √((8)^2 + (6)^2)

d = √(64 + 36)

d = √(100)

d = 10 units

1 unit = 100 yards

Therefore, 10 units = 1,000 yards.

Kate and Ben's House are 1,000 yards apart.

b. Since Jason's home is halfway between Ben and Kate's House, therefore, Jason's location is the midpoint between Ben and Kate's House. Use the midpoint formula to calculate the coordinates of Jason's location on the map, using (6, 2) and (-2, -4).

M((x_1 + x_2)/(2), (y_1 + y_2)/(2))

Plug in the values

M((6 +(-2))/(2), (2 +(-4))/(2))

M((4)/(2), (-2)/(2))

M(2, -1)

Plz helpp


I’ll mark you brainliest

Answers

Answer:52°

Step-by-step explanation:

x+x+14=90

Collect like terms

x+x=90-14

2x=76

Divide both sides by 2

2x/2=76/2

x=38

angle (x+14)°=(38+14)°=52° which is vertically opposite to angle PKQ.

Since Vertically opposite angles

Therefore angle PKQ=52

A local department store sells carpet in 4 sizes . Each carpet comes in 3 different qualities. One of the size come in 5 colors . The other sizes come in 3 colors . How many choices of carpet are there?

Answers

The total number of choices is 42 if a local department store sells carpets in 4 sizes. Each carpet comes in 3 different qualities. One of the sizes comes in 5 colors.

What are permutation and combination?

A permutation is the number of different ways a set can be organized; order matters in permutations, but not in combinations.

It is given that:

A local department store sells carpets in 4 sizes.

Each carpet comes in 3 different qualities.

One of the sizes comes in 5 colors.

The other sizes come in 3 colors.

The number of choices can be found as follows:

= 1x3x5

= 15

= 3x3x3

= 27

Total number of choices = 15 +27

= 42

Thus, the total number of choices is 42 if a local department store sells carpets in 4 sizes. Each carpet comes in 3 different qualities. One of the sizes comes in 5 colors.

Learn more about permutation and combination here:

brainly.com/question/2295036

#SPJ2

there are 60 choices of carpet

reason:
4*3*5
12*5
=60
or
4*3*5
4*15
=60

Jay simplify the expression 3x( 3+12÷3)-4 over his first step he added 3+12 to get 15 what was jays error? Find the correct answer

Answers

Hello there!

To simplify this expression, you must follow PEMDAS.

3x(3+12÷3) parentheses first
3x(3+4) do the division
3x(7) addition inside of parentheses
21x multiplication

This means that Jay is incorrect in doing addition first.

I really hope this helps!
Best wishes :)
distribute 3x through all the numbers in () then solve for x and you get 21x-4